Colorado! - Ross, Dana Fuller (New York Bantam Books, 1981)
Denver! Braving the Rockies and the untamed wilderness, they came to the wild frontier town and watched it explode into a city of fabulous instant wealth. Some were desperate men and women fleeing the mounting turbulence in the East, others were adventurers forsaking the played-out dreams of the California gold fields. They were lured by the most powerful promise of all--bonanza!
Includes an excerpt from Amazons, by Roy Sparkia.
89584
Keywords: Frontier and pioneer life -- Colorado -- Fiction; Gold mines and mining; Historical fiction